Opinion Leadership and Achievement of Sustainable Health Care in Nigeria: Analyzing the Two-Step Flow Paradigm - Ifeanyi Nwokeocha (Jurnal Multidisiplin Madani, 2023)
This study examined the influence of opinion leadership in the achievement of sustainable health care delivery in Nigeria using this two-step flow paradigm. Two previous studies were reviewed as related to the study and the two-step flow theory was used to provide the theoretical background to the study. The paper recommended that there should be functional and competent evaluation systems to track progress and challenges in the health sector at all levels of operation and periodical reviews done to improve the quality of care, the influence of opinion leaders should not be neglected because they can be used to interpret health policies thereby helping the government get the desired outcomes or shape certain opinions, especially on health issues, etc